Supplement to Actualism

Proof of NE in SQML

Theorem (NE):x□∃y(y=x)

Proof:

(1) x = x identity axiom
(2) y(yx) → xx quantifier axiom
(3) x = x → ¬∀y(yx) from (2), by propositional logic
(4) x = x → ∃y(y = x) from (3), by definition of ∃ and propositional logic
(5) y(y = x) from (1) and (4), by MP
(6) □∃y(y = x) from (5), by RN
(7) x□∃y(y = x) from (6), by GEN

Copyright © 2014 by
Christopher Menzel <cmenzel@tamu.edu>

Open access to the SEP is made possible by a world-wide funding initiative.
Please Read How You Can Help Keep the Encyclopedia Free


The SEP would like to congratulate the National Endowment for the Humanities on its 50th anniversary and express our indebtedness for the five generous grants it awarded our project from 1997 to 2007.